Respect for Labor - M. Tayfun Gülle (Türk Kütüphaneciliği)
For almost the past thirty years, there has been an increase in the exploitation of human labor, especially in developed and developing nations, mostly due to rapid globalization. Turkish librarians and information providers believe that they have been impacted by this phenomenon. In order to solve the problem of pay inequity that exists among professionals in this sector, the President of the Turkish Librarian’s Association (TLA), Ali Fuat Kartal, has appealed to the Turkish cabinet for assistance and has also placed his thoughts into writing as conveyed by the following editorial, which summarizes the injustices plaguing the Turkish system. This editorial also discusses the process involved in the creation of an open access archive for Turkish Librarianship Journal (TL); the entry of the TL into the DOAJ (Directory of Open Access Journals); the wealth of social media resources included on the TLA’s website; and the need to respect the efforts of Turkish librarians and information providers.